Análisis de los efectos en la estructura agraria y rural integral del acuerdo Final para La Terminación del Conflicto y la Construcción de una Paz Estable y Duradera en Colombia (2020)
Following the constant problem of violence and underdevelopment in Colombia, the comprehensive agricultural and rural structure is analyzed on the basis of the peace agreement as the various substantive problems present in the country and in some countries can be highlighted region. In turn, we understand the pre- and during-peace stages of the agricultural and rural structure in a shift-mandate measurement environment as Colombia has suffered from strong public policies focused on the field and have created strong imbalances in both the use and tenure of the land, since this means the internal armed conflict is caused by both guerrillas, paramilitaries and the National Army for more than 50 years.